Implementation of Health Education on Danger Signs of Pregnancy to Improve the Knowledge of Pregnant Women - Rugun Togianur Lingga; Heriaty Berutu; Tiurlan M Doloksaribu; Verawaty Fitrinelda Silaban (GLOBAL HEALTH SCIENCE GROUP, 2026)
Pregnancy is a crucial period in a woman’s life, where the health of both mother and fetus requires special attention. One of the efforts to prevent complications is providing health education regarding the danger signs of pregnancy. This study aims to determine the effect of health education on improving pregnant women’s knowledge about pregnancy danger signs in the working area of Sitinjo Health Center. This research employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 pregnant women in their second and third trimesters, selected using purposive sampling. Data were analyzed using the Wilcoxon Signed Rank Test. The results indicated a significant increase in pregnant women’s knowledge after receiving health education, with a p-value < 0.05. Prior to the intervention, most respondents had low to moderate knowledge, while after the intervention the majority demonstrated good knowledge. This finding confirms that health education is effective in enhancing pregnant women’s understanding of pregnancy danger signs. Improved knowledge is expected to encourage pregnant women to be more alert regarding their pregnancy conditions, thereby preventing delays in handling complications. Therefore, health education should be continuously implemented by health workers in primary care settings.